Breach of Contract: A Comparison Between Indonesian and Malaysian Contract Law - Yati Nurhayati; Mohd Zamre Mohd Zahir; Muhammad Hatta; Muhammad Hendri Yanova; Parman Komarudin (International Journal of Law, Environment, and Natural Resources, 2022)
The purpose of this research study aims to dissect the concept of Breach of contract in the civil law of two countries between Indonesia and Malaysia. As a country that has a different legal system but also recognizes Breach of contract or breaking promises in civil relations. In this research method, the type of research that the author uses is normative research. The nature of the research in this paper is the nature of comparative descriptive research. The approach used in this legal research is the statute approach, and the conceptual approach. The results of the study found that the Breach of contract in Indonesian civil law. This is a deviant act committed by one of the parties to the agreement from what was previously agreed without coercion which can result in losses for the opposing party and default in civil law in Malaysia as regulated in the 1950 Contract Law which is called Contract impossibility, a contract may be terminated. If the contracting parties fail to carry out the responsibilities contained in the contract.